(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Tourism industry experiencing rapid development. Its role is important in the processes of spatial organization of social life and the formation of sustainable human development. The main issue is the creation of a sustainable touristic model. In this matter, four principles of geographical approach can play an important part: territoriality, complex approach, concreteness and globality, which, with the integrated application of all components of the geographic environment, contribute to the creation of a sustainable tourism model.